dTtc1, a conserved tetratricopeptide repeat protein, is required for maturation of Drosophila egg chambers via its role in stabilizing electron transport chain components - Neiswender, Hannah; Baker, Frederick C.; Veeranan-Karmegam, Rajalakshmi; Allen, Phylicia; Gonsalvez, Graydon B. (Frontiers in Cell and Developmental Biology, 2023)
We recently identified the Drosophila ortholog of TTC1 (dTtc1) as an interacting partner of Egalitarian, an RNA adaptor of the Dynein motor. In order to better understand the function of this relatively uncharacterized protein, we depleted dTtc1 in the Drosophila female germline. Depletion of dTtc1 resulted in defective oogenesis and no mature eggs were produced. A closer examination revealed that mRNA cargoes normally transported by Dynein were relatively unaffected. However, mitochondria in dTtc1 depleted egg chambers displayed an extremely swollen phenotype. Ultrastructural analysis revealed a lack of cristae. These phenotypes were not observed upon disruption of Dynein. Thus, this function of dTtc1 is likely to be Dynein independent. Consistent with a role for dTtc1 in mitochondrial biology, a published proteomics screen revealed that dTtc1 interacts with numerous components of electron transport chain (ETC) complexes. Our results indicate that the expression level of several of these ETC components was significantly reduced upon depletion of dTtc1. Importantly, this phenotype was completely rescued upon expression of wild-type GFP-dTtc1 in the depleted background. Lastly, we demonstrate that the mitochondrial phenotype caused by a lack of dTtc1 is not restricted to the germline but is also observed in somatic tissues. Our model suggests that dTtc1, likely in combination with cytoplasmic chaperones, is required for stabilizing ETC components.